Documenting Physical Therapy Dose for Individuals With Cerebral Palsy: A Quality Improvement Initiative. Issue 3 (July 2019) - Bailes, Amy F.; Strenk, Mariann L.; Quatman-Yates, Catherine; Hobart, Jessica; Furnier, Adam
Abstract : Purpose: To describe the quality improvement (QI) activities used to improve treatment dose documentation for individuals with cerebral palsy (CP) and to discuss insights gained from this project. Methods: Global and smart aims were established and interventions were tested from January 2017 through February 2018 using Plan-Do-Study-Act cycles. Performance was tracked overtime using run and control charts. Results: The QI initiative resulted in a sustainable increase in percentage of dose elements present in the electronic medical record from 78% to 94%. Key drivers of improvement included (1) knowledge and awareness of dose, (2) clinician buy-in, (3) effective engagement of child and parent, (4) therapist knowledge of evidence-based treatments, (5) transparent and reliable documentation system, and (6) audit and clinician feedback. Conclusions: QI methods provided the tools to improve workflow and increase dose documentation for individuals with CP. Abstract : Supplemental Digital Content is Available in the Text.Describes the quality improvement activities used to improve treatment dose documentation for individuals with cerebral palsy and to describe insights gained from this project.